2017
DOI: 10.1002/ejp.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a psychosocial intervention programme combined with exercise in community‐dwelling older adults with chronic pain: A randomized controlled trial

Abstract: Although research has shown that combined exercise and psychosocial intervention is optimal for managing chronic pain, our study is the first, to the best of our knowledge, to test a specific intervention of this type in community-dwelling older adults with chronic pain in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Again, to the best of our knowledge, no previous studies have investigated the preventive effects of a community-based intervention program on pain in community-dwelling older adults without chronic pain, as most studies have targeted individuals with chronic pain [ 1 , 12 , 14 ]. In previous animal model studies that used mice, Sluka et al [ 13 ] reported that an 8-week wheel-running activity intervention effectively prevented decreases in muscle withdrawal thresholds and increased responses to mechanical stimulation of the paw for up to 72 hours after the noninflammatory pain model was induced with two injections of unbuffered pH 4.0 saline into one gastrocnemius muscle 5 days apart, compared with sedentary controls.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Again, to the best of our knowledge, no previous studies have investigated the preventive effects of a community-based intervention program on pain in community-dwelling older adults without chronic pain, as most studies have targeted individuals with chronic pain [ 1 , 12 , 14 ]. In previous animal model studies that used mice, Sluka et al [ 13 ] reported that an 8-week wheel-running activity intervention effectively prevented decreases in muscle withdrawal thresholds and increased responses to mechanical stimulation of the paw for up to 72 hours after the noninflammatory pain model was induced with two injections of unbuffered pH 4.0 saline into one gastrocnemius muscle 5 days apart, compared with sedentary controls.…”
Section: Discussionmentioning
confidence: 99%
“…We asked participants in both groups to attend a 60 min weekly exercise class for 12 weeks. The class comprised 10 min of warm-up, 20 min of strength training, 20 min of balance training, and 10 min of cool-down, as described in our previous study [ 14 ]. All classes involved approximately 10 participants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations